2022
DOI: 10.1556/2006.2022.00056
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between parental involvement and internet gaming disorder among Chinese adolescents: Consideration of future consequences as a mediator and peer victimization as a moderator

Abstract: Background and aims Internet gaming disorder (IGD) in adolescents is a concerning issue. Positive parenting has been found to protect against adolescent IGD, but the underlying mechanisms await further investigation. As such, this study examined the longitudinal association between parental involvement (PI) – a specific type of positive parenting understudied in the literature of adolescent gaming disorder – and IGD. Moreover, this study also tested consideration of future consequences (CFC) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…To our knowledge, this study is the first to find the indirect association of positive parenting behavior with PVG. The direct association of negative parenting behavior is consistent with a study reporting the negative association between parental involvement and IGD (Dou et al, 2022). Family functioning was not associated with either GD or IGD in any of the regression models in this study, although correlated with child-reported IGD and parent-reported GD/IGD.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this study is the first to find the indirect association of positive parenting behavior with PVG. The direct association of negative parenting behavior is consistent with a study reporting the negative association between parental involvement and IGD (Dou et al, 2022). Family functioning was not associated with either GD or IGD in any of the regression models in this study, although correlated with child-reported IGD and parent-reported GD/IGD.…”
Section: Discussionsupporting
confidence: 91%
“…A higher mean score indicated a high level of perceived peer victimization. This scale has been demonstrated to be valid and reliable among Chinese adolescents [ 31 ]. McDonald’s omega was 0.64.…”
Section: Methodsmentioning
confidence: 99%
“…Parent-adolescent conflict not only prevents adolescents from meeting their increasing need to develop autonomy and individuation but also affects adolescents’ emotional insecurity and insecure attachment [ 19 ]. Therefore, adolescents may rely on Internet use to meet their unfulfilled social and psychological needs left unmet by their families [ 20 , 21 ]. Moreover, parent-adolescent conflict is a main source of stress in the early stage of individual development [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown a strong direct association between parent-adolescent conflict and depression [ 31 , 32 ]. To relieve negative emotions, adolescents with depression may turn to increase Internet use to enhance their mood and compensate for unmet needs caused by parent-adolescent conflict [ 20 , 23 , 33 ]. In addition, depression can deplete adolescents’ self-control resources, leading to a lack of self-control [ 34 ].…”
Section: Introductionmentioning
confidence: 99%